2015
DOI: 10.1097/ncc.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychological Predictors of Quality of Life in Chinese Colorectal Cancer Patients During Chemotherapy

Abstract: Enhanced self-efficacy, reduced symptom distress, and lower general anxiety would improve QOL during chemotherapy for CRC patients.These instruments can help identify CRC patients at risk of low QOL for additional psychotherapy or specific treatment modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
3
19
0
5
Order By: Relevance
“…By contrast, men tend to hide their vulnerability and may not accurately report the severity of their symptoms in a survey setting (Haj et al, ). This study found that a higher stage of disease was associated with the severity of the symptom clusters, which is consistent with previous studies (Zhang et al, ). In addition, a negative relationship was found between resilience and the severity of the symptom clusters.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, men tend to hide their vulnerability and may not accurately report the severity of their symptoms in a survey setting (Haj et al, ). This study found that a higher stage of disease was associated with the severity of the symptom clusters, which is consistent with previous studies (Zhang et al, ). In addition, a negative relationship was found between resilience and the severity of the symptom clusters.…”
Section: Discussionsupporting
confidence: 93%
“…Greater self‐efficacy has been reported to be associated with better symptom management, improved functioning and higher QoL scores (Akin et al., ; Cunningham et al., ; Curtis et al., ; Kiaei, ; Kreitler et al., ; Lev et al., ; Liang et al., ; Zhang et al., , ). For instance, a study conducted by Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study conducted by Zhang et al. (, ) found that greater self‐efficacy in patients with colorectal cancer undergoing adjuvant chemotherapy was associated with fewer daily life impairments and distress symptoms. Another study reported that the higher fatigue scores in patients with breast cancer were significantly related to lower self‐efficacy in physical activity scores (Haas, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible explanations are as follows: first, those having received chemotherapy may have benefited more from the inhibition of disease progress, which would result in low levels of psychological distress. Second, there was a decline in depression, anxiety, and the impact of the adverse effects of chemotherapy in patients with the passing of time because of the acceptance of the diagnosis and management 5153…”
Section: Discussionmentioning
confidence: 99%